Life in two countries but one home land – Béla Lipthay (1892-1974) the entomologist - Bozsik, András (Acta Agraria Debreceniensis, 2014)
Béla Lipthay lepidopterologist, entomologist, museologist, agriculturist, hussar lieutenant, life-saving Roman Catholic, descendant of the historical family Lipthay de Kisfalud et Lubelle did a long way from his home village Lovrin to Szécsény, the one-time land of his ancestors. His life coincided with the disintegration of the historical Hungary, and the most serious trials of the Hungarian society, culture and spirit. These changes affected him as a member of Hungarian aristocracy many times and in fact wanted to destroy him. The fortune of the ancestors have been swept away by the storms of the wars and confiscated but the human strength of character, the consciousness, the talent, the diligence, the sanctuary of faith have remained. All these made him possible to survive, to do his everyday hard creative work, which gained him affection and respect of the people living around him.Lipthay Béla was mainly lepidopterist and dealt with the the species of Hungary. Place of his collection was first his native country, the Banat, and the area of the Southern Carpatian Montain, and after 1944 Nógrád county (Szécsény, Balassagyarmat, Nógrádszakál, Ipolytarnóc, Rimóc, Ludányhalászi etc.). The collected species belonged to Macrolepidoptera but he dealt also with the moths. During his life time he prepared a collection of 60000 individuals and maintained them until his passing away. Great part of this collection can be found at the zoological cabinet of Natural History Museum in Budapest. He discovered many species new for the Hungarian fauna such as e.g. Cupido osiris (Meigen, 1829), and described a new species (Chamaesphecia sevenari Lipthay, 1961) which later proved to be a synonym of Chamaesphecia nigrifrons (Le Cerf, 1911). He knew well the most famous collectors and specialists of the age. After the first World War he worked together with Frigyes König, László Diószeghy, Jenő Teleki, Norman D. Riley (leading entomologist of the British Museum at London, secretary of the Royal Entomological Society), Brisbane C. S. Warren ( member of the Royal Entomological Society), Lionel W. Rothschild (the most important private collector) and many excellent lepidopterists. After the second World War he was well known and respected by the Hungarian entomologists and lepidopterists: he was a friend of Lajos Kovács, the distinguished lepidopterist and Zoltán Kaszab, the eminent entomologist. He had a good relationship with such renowned Hungarian zoologists and entomologists like Gyula Éhik, László Gozmány, László Issekutz, László Bezsilla and László Móczár. He colleted also Hymenoptera, Diptera and capricorn beetles to be found in Hungarian and foreign collections Natural History Museum, (London), a Szekler National Museum (Marosvásárhely). He dealt with agricultural entomology because he was an experienced agriculturist as far as he had the opportunity to do that. He painted wonderful agricultural entomology posters and organized expositions e.g. on the pests of industrial crops and hunting at Balassagyarmat and Salgótarján.